Hermeneutiese uitgangspunte in historiese-Jesus navorsing, Deel 1: Sosiaal-wetenskaplike vooronderstellings P A Geyser - Geyser, P. A. (Hervormde teologiese studies, 2000)
Hermeneutical premises in historical Jesus research, Part 1:social-scientific presuppositions. The aim of this article is to reflect on social-scientific theoies, models and methods in historical Jesus research. The discussion focuses on ive epistemological aspects. The first aspect is the social conditioning of the epistemological process. All knowledge is socially conditioned and perspectival in nature. The second aspect is the situational discourse of the interpreter and the object of investigation. The third aspect concerns the process of knowing where theories and models are discussed. Distinctions are drawn between paradigms, theories, models and methods. Heuristics is the fourth matter to be discussed. Three approaches are evaluated critically: deduction, induction and abduction. Fifthly, the world of the Bible will be considered as a pre-industrial and advanced agrarian society.